COMPARATIVE ANALYSIS OF THE OPINIONS OF YUSUF AL-QARADAWI AND FAQIHUDDIN ABDUL QADIR ON THE LAW OF POLYGAMY - Brillianty, Nadia Aqila; Ulya, Zakiyatul (UIN Sayyid Ali Rahmatullah Tulungagung, 2025)
Polygamy is one of the issues that often becomes a debate in the study of Islamic family law, both in terms of legality, ethics, and social aspects. This article aims to analyze the similarities and differences in the opinions of contemporary scholars, namely Yusuf Al-Qaradawi and Faqihuddin Abdul Qadir, regarding the legality of polygamy, including the legal basis and the interpretation of justice as its condition. This study is a literature review with documentation as the data collection technique and a comparative study as the analysis technique. The similarities between the two figures are that they both permit polygamy, use Surah An-Nisa verse 3 as the legal source for polygamy, and regard justice as the primary condition for allowing polygamy. The differences are that Yusuf Al-Qaradawi considers polygamy to be a solution, understands Surah An-Nisa verse 3 in isolation, and views justice in polygamy only in material terms such as financial support, housing, clothing, and time spent together. Meanwhile, Faqihuddin Abdul Qadir argues that polygamy cannot be seen as a solution as it potentially brings harm to the family, interprets Surah An-Nisa verse 3 not in isolation but in conjunction with the preceding and following verses, which are verses 2 and 4, and believes that justice in polygamy encompasses all aspects, including immaterial elements such as emotions.